Degradation kinetics of Endosulfan isomers by micron‐ and nano‐sized zero valent iron particles (MZVI and NZVI). Issue 8 (9th October 2015) - Singh, Swatantra Pratap; Bose, Purnendu
Abstract: BACKGROUND: The pesticide Endosulfan is commercially available as a mixture of two conformal isomers, i.e. Endosulfan‐1 (Endo‐1) and Endosulfan‐2 (Endo‐2). Endosulfan has been characterized as extremely toxic by USEPA and is persistent in nature. In this study micron‐ and nano‐sized zero‐valent iron particles (MZVI and NZVI) were used for rapid degradation of the Endosulfan isomers. RESULTS: Both Endo‐1 and Endo‐2 undergo abiotic hydrolysis resulting in the formation of equi‐molar quantities of Endosulfan alcohol. During interaction with MZVI, the degradation rates of both Endo‐1 and Endo‐2 were observed to be pseudo‐first‐order and the surface normalized degradation rate constants ( ks ) were 6.33 × 10 −4 L h −1 m −2 and 6.38 × 10 −4 L h −1 m −2 for Endo‐1 and Endo‐2, respectively. During interaction with NZVI, ks values for Endo‐1 and Endo‐2 were 2.58 × 10 −2 L h −1 m −2 and 1.21 × 10 −2 L h −1 m −2, respectively. GC‐MS analysis showed evidence of the formation of partially dechlorinated by‐products due to Endo‐1 and Endo‐2 interactions with MZVI and NZVI. CONCLUSIONS: Surface area normalized degradation rate constants ( ks ) for Endo‐1 and Endo‐2 degradation by NZVI were 40 and 19 times higher, respectively, than the corresponding values by MZVI. This indicates higher reactivity of the NZVI surface vis‐à‐vis Endo‐1 and Endo‐2 degradation. Partially dechlorinated by‐products observed during interaction of Endo‐1 and Endo‐2 with NZVI and MZVI may be less toxic and more amenable to subsequent biodegradation than the parent compounds. © 2015 Society of Chemical Industry